Control and Management of Hypertension at a University Health Centre in Oman - Abdulaziz Almahrezi; Ibrahim Al-Zakwani; Ayman Al-Aamri; Samia Al-Khaldi; Nisrin Al-Zadjali; Mohammed Al-Hatali; Abdullah Al-Shukeili (Sultan Qaboos University Medical Journal, 2008)
Objectives: To evaluate the prevalence of hypertension, its control and management at Sultan Qaboos University (SQU) Health Centre, Oman. Methods: This was a retrospective cross-sectional study, in which were enrolled all the subjects (≥18 years), with the diagnosis of essential hypertension, who attended the SQU Health Centre between 1998 and 2002. The systolic and diastolic blood pressure (BP) values of the last three visits were used for analysis. BP control was defined using the Joint National Committee (JNC-7) criteria, <140 mmHg and <90 mmHg for systolic and diastolic BPs, respectively. Analyses were performed using univariate statistics. Results: Among the 7,702 medical records reviewed, the prevalence of hypertension was 2.4% (n = 187). The overall mean age of the cohort was 55±11 years, 54% (n = 101) were females, and majority of the subjects were Omanis (n = 123; 66%). The proportion of subjects who had their BP controlled was 41% (n = 77) with Omanis significantly less likely to have their BP controlled compared to non-Omanis (53% versus 35%; p = 0.017). The majority of the subjects were on mono (n = 131; 70%) followed by dual (n = 50; 27%) anti-hypertensive therapies. The most frequent mono anti-hypertensive therapies were B-blockers (n = 64; 34%) and angiotensin-converting enzyme (ACE) inhibitors (n = 47; 25%). Among the dual combination therapies, the most common prescribed regimens were ACE inhibitor plus B-blocker (n = 14; 28%) and B-blocker plus diuretic (n = 12; 24% ). Conclusion: The prevalence of hypertension in this patient population was low compared to the national average. This study shows that control of hypertension is not optimal, but higher than those reported elsewhere.